Peptidylarginine Deiminase Inhibition Abolishes the Production of Large Extracellular Vesicles From Giardia intestinalis, Affecting Host-Pathogen Interactions by Hindering Adhesion to Host Cells - Gavinho, Bruno; Sabatke, Bruna; Feijoli, Veronica; Rossi, Izadora Volpato; da Silva, Janaina Macedo; Evans-Osses, Ingrid; Palmisano, Giuseppe; Lange, Sigrun; Ramirez, Marcel Ivan (Frontiers in Cellular and Infection Microbiology, 2020)
Giardia intestinalis is a microaerophilic protozoan that is an important etiologic agent of diarrhea worldwide. There is evidence that under diverse conditions, the parasite is capable of shedding extracellular vesicles (EVs) which modulate the physiopathology of giardiasis. Here we describe new features of G. intestinalis EV production, revealing its capacity to shed two different enriched EV populations: large (LEV) and small extracellular vesicles (SEV) and identified relevant adhesion functions associated with the larger population. Proteomic analysis revealed differences in proteins relevant for virulence and host-pathogen interactions between the two EV subsets, such as cytoskeletal and anti-oxidative stress response proteins in LEVS. We assessed the effect of two recently identified inhibitors of EV release in mammalian cells, namely peptidylarginine deiminase (PAD) inhibitor and cannabidiol (CBD), on EV release from Giardia. The compounds were both able to effectively reduce EV shedding, the PAD-inhibitor specifically affecting the release of LEVs and reducing parasite attachment to host cells in vitro. Our results suggest that LEVs and SEVs have a different role in host-pathogen interaction, and that treatment with EV-inhibitors may be a novel treatment strategy for recurrent giardiasis.